KEBEBASAN AKADEMIS DALAM TRADISI INTELEKTUAL MUSLIM - Muhammad Roihan Daulay (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2016)
This article consisted of the academician’s freedom in Islamic intellectual tradition. The existence of Islam in this world is the greatest tendency, called rahmatan lil’alaminwhich is proved globally of long history. In Islam, the freedom of ideology about life’s regulation is totally clear and it is signed by syumuliah (universalism) as a system of life particularly in Islamic intellectual tradition.